About the charge transfer in the graphene lattice - B. V. Alexeev; I. V. Ovchinnikova (Тонкие химические технологии)
The charged particles motion in graphene under the influence of an external electric field in the frame on the nonlocal quantum hydrodynamic description is considered. With the help of the numerical solution of a system of nonlocal hydrodynamic equations the dependence of the soliton structures on the external electric field is investigated